Tolerance and bioaccumulation of combined copper, zinc, and cadmium in Sesuvium portulacastrum. (June 2018) - Feng, Jianxiang; Lin, Yanyan; Yang, Yao; Shen, Qianqian; Huang, Jianrong; Wang, Shugong; Zhu, Xiaoshan; Li, Zufu
Abstract: Sesuvium portulacastrum was treated with mixture of copper, zinc, and cadmium for 60 days, with the concentration of each metal ranging from 0 to 20 mg/L. The tolerance of plants and bioaccumulation of heavy metals were then investigated. The height of S. portulacastrum decreased significantly with increasing heavy metal concentrations from 1 to 20 mg/L. The biomass was adversely impacted when the concentration exceeded 5 mg/L. There were no significant differences in malondialdehyde (MDA) concentration among different treatment groups, while the soluble protein content and superoxide dismutase (SOD) activity decreased with increasing heavy metal concentration. However, the BCF values of the three metals were all higher than 10 and the tolerance in root was up to 1000 mg/kg without causing significant growth inhibition, suggesting that S. portulacastrum should be a potential candidate for phytostabilization for the phytoremediation of polymetallic contaminations in coastal environments. Highlights: Tolerance and bioaccumulation of combined Cd, Cu and Zn were investigated in Sesuvium portulacastrum . The growth of S. portulacastrum were affected when the combined heavy metal concentration exceeded 1mg/L. S. portulacastrum showed high BCF values but low TF values for combined Cd, Cu and Zn. S. Portulacastrum can be potentially used for phytostabilization in coastal environments under Cd, Cu and Zn contamination.